2020
DOI: 10.1038/s41598-020-60953-z
|View full text |Cite
|
Sign up to set email alerts
|

Human glutaredoxin-1 can transfer copper to isolated metal binding domains of the P1B-type ATPase, ATP7B

Abstract: Intracellular copper (Cu) in eukaryotic organisms is regulated by homeostatic systems, which rely on the activities of soluble metallochaperones that participate in Cu exchange through highly tuned protein-protein interactions. Recently, the human enzyme glutaredoxin-1 (hGrx1) has been shown to possess Cu metallochaperone activity. The aim of this study was to ascertain whether hGrx1 can act in Cu delivery to the metal binding domains (MBDs) of the P 1B-type ATPase ATP7B and to determine the thermodynamic fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…While the inactivation of the glutaredoxin-like N-MBS1 can be fully restored by Cu supplementation, the CopZ-like N-MBS2 yielded an intermediate phenotype that could only be rescued partially by Cu addition. Considering that the CopZ-like N-MBS2 is conserved between CcoI and CopA, while the presence of the N-MBS1 is a particular feature of the high-affinity CcoI, these findings suggested that N-MBS1 might be important for receiving Cu from an alternative Cu donor different than CopZ, such as glutaredoxin or even glutathione ( Maghool et al, 2020 ; Stewart et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While the inactivation of the glutaredoxin-like N-MBS1 can be fully restored by Cu supplementation, the CopZ-like N-MBS2 yielded an intermediate phenotype that could only be rescued partially by Cu addition. Considering that the CopZ-like N-MBS2 is conserved between CcoI and CopA, while the presence of the N-MBS1 is a particular feature of the high-affinity CcoI, these findings suggested that N-MBS1 might be important for receiving Cu from an alternative Cu donor different than CopZ, such as glutaredoxin or even glutathione ( Maghool et al, 2020 ; Stewart et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…While the TM-MBSs are essential for Cu translocation ( Gonzalez-Guerrero et al, 2008 , 2009 ), the N-MBSs in bacterial CopA-like ATPases appear to be non-essential ( Fan et al, 2001 ; Gonzalez-Guerrero and Arguello, 2008 ; Drees et al, 2015 ). Instead, they are proposed to regulate the ATPase activity in response to Cu availability ( Wu et al, 2008 ; Arguello et al, 2016 ) and to support Cu-loading of the TM-MBSs ( Figure 7 ; Drees et al, 2015 ; Maghool et al, 2020 ). Current models suggest that in the absence of Cu, the N-MBS is interacting with the N- and the A-domains of CopA, preventing either ATP binding or phosphorylation of the P-domain ( Tsivkovskii et al, 2001 ; Wu et al, 2008 ; Gonzalez-Guerrero et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One hypothesis for this specificity that had been proposed is that the proline in the GRX active site prevents metal binding and/or the dimerization required for metal transfer [14]. However, more recent research has indicated that copper ions can bind within GRX's active site unhindered by these prolines [15,16]. Instead, other metallochaperones, such as ATOX1, with a higher metal affinity, outcompete GRX for metal cations [15].…”
Section: Introductionmentioning
confidence: 99%
“…In human cells, after copper transporter protein 1 (Ctr1)-mediated uptake, the cytoplasmic Cu chaperone Atox1 transports Cu to ATP7A and ATP7B in the trans-Golgi network (Puig and Thiele 2002). In support of possible redundancy, it was recently shown that glutaredoxin 1 could replace Atox1 and deliver Cu to ATP7B (Maghool et al 2020). ATP7A/B are P 1B -type ATPases that use ATP hydrolysis to transfer Cu to the lumen for loading of target Cu-dependent enzymes, such as ceruloplasmin, tyrosinase and lysyl oxidase (Matson Dzebo et al 2016).…”
Section: Introductionmentioning
confidence: 99%